Food preferences and response to novel native berries by captive-reared Nene Branta sandvicensis goslings - Rojek, Nora A; Conant, Sheila (Wildfowl, 1996)
Food choice experiments conducted on captive Nene goslings confirmed significant preferences among the food items offered which could not be attributed to protein or water content. Grain (cracked corn and wheat) and Pualele were preferred significantly over all other items offered. Goslings that had been reared on the typical captive diet (Standard Diet) for 40 days did not differ in the average consumption of novel native berries from goslings that had been raised from Day 1 with exposure to berries (Enhanced Diet). From Days 40 to 44, however, gosling groups did differ significantly in their relative preference for different berries, with Standard Diet birds preferring Kukaenene berries and Enhanced Diet birds preferring Ohelo berries. Nene that had remained in captivity until adulthood on a limited diet did not accept novel foods as readily as goslings. Adult nene that had been captive-reared did not readily try the novel berries whereas wild-caught adult Nene in captivity did recognize and consume the berries. The results of this study indicate that feeding native berries to captive-reared goslings is not likely to influence the diet of Nene released into the wild as fledglings. The length of time in captivity, however, is important in considering the diet to be offered to Nene reared for eventual release.